2014
DOI: 10.1111/joca.12057
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a Financial Education Curriculum as an Intervention to Improve Financial Behaviors and Financial Well‐Being of Survivors of Domestic Violence: Results from a Longitudinal Randomized Controlled Study

Abstract: The Allstate Foundation and the National Network to End Domestic Violence created a financial education curriculum to improve individual financial management skills and, ultimately, to improve domestic violence survivors' financial well‐being. This study, guided by the reasoned action approach, evaluates their curriculum using a longitudinal randomized control study, with data collected over four time periods spanning 14 months. The analyses demonstrated that the treatment group had an average improvement betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 18 publications
(24 reference statements)
1
45
0
3
Order By: Relevance
“…Moreover, the objective measure is the resource input in financial education, such as time and money. Using the sampling data of survivors of domestic violence, Postmus et al [49] indicated that survivors of domestic violence improved their personal financial management skills through training courses of financial education, and ultimately, improved their own life satisfaction. There is also evidence that some social workers had their living costs increased due to the global recession, and their real incomes had declined [50].…”
Section: The Impact Of Sustainable Financial Education and Consumer Lmentioning
confidence: 99%
“…Moreover, the objective measure is the resource input in financial education, such as time and money. Using the sampling data of survivors of domestic violence, Postmus et al [49] indicated that survivors of domestic violence improved their personal financial management skills through training courses of financial education, and ultimately, improved their own life satisfaction. There is also evidence that some social workers had their living costs increased due to the global recession, and their real incomes had declined [50].…”
Section: The Impact Of Sustainable Financial Education and Consumer Lmentioning
confidence: 99%
“…Finally, in their study, “Evaluating a Financial Education Curriculum as an Intervention to Improve Financial Behaviors and Financial Well‐Being of Survivors of Domestic Violence: Results from a Longitudinal Randomized Controlled Study,” Postmus, Hetling, and Hoge () address financial capability in a specific vulnerable population. Their evaluation of a financial education curriculum for survivors of domestic violence finds improvements in financial knowledge, financial intentions, and financial behavior as well as a reduction in financial strain.…”
Section: Action For Financial Capabilitymentioning
confidence: 99%
“…An intervention of this type would rely theoretically on COR and focus on protecting or minimizing the loss of financial resources. A recent study demonstrated that an intervention to reduce financial insecurity through learning basic fundamentals of personal finance can be successful (Postmus, Hetling, & Hoge, ). Providing training to victims of domestic violence, Postmus et al .…”
Section: Discussionmentioning
confidence: 99%
“…Providing training to victims of domestic violence, Postmus et al . () focused on several components: mastering credit basics, building financial foundations, and creating budget strategies. Authors showed success through improvements over time of financial knowledge, intentions to perform financial behaviours, and the participants’ actual financial behaviours.…”
Section: Discussionmentioning
confidence: 99%